(untitled) (Journal of Association of Educational Management and Policy Practitioners, 2025)
This study aims to analyse the implications of the funding structure in Nigerian secondary schools for school managers. The study has two main objectives. Firstly, to explore the challenges posed by the lack of a viable funding structure in Nigerian secondary schools and, secondly, to identify strategies school managers can employ to ensure they operate in an economically sustainable manner. To meet these objectives, a qualitative study was conducted using semi-structured interviews as the main data collection tool. Participants included school managers, senior staff, teachers, and learners in two Nigerian Secondary schools in two locations. Results of the study revealed that the lack of a viable funding structure for Nigerian secondary schools poses many challenges for school managers. These challenges generally relate to the overall quality of the educational service, which is impacted by the lack of adequate resources. The study also identified key strategies that can be employed by school managers to manage the difficult economic situation of their schools. These included the need to use available resources efficiently and effectively, create alternative sources of revenue, and build partnerships with other stakeholders. The results of this study provide useful insights into the implications of the lack of a viable funding structure for Nigerian secondary schools, as well as strategies that school managers can employ to ensure their schools are financially sustainable. These findings could inform future interventions and policymaking designed to improve the funding structure of Nigerian secondary schools.